A critical evaluation of bilingual Chinese/English dictionaries for elementary and intermediate Mandarin learners at Stellenbosch University - Wang, Mei (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.